Some examples of treatment for the aortic aneurysm in use during the Belle Époque - Cozza, Andrea; Armocida, Emanuele; Grego, Franco; Rippa Bonati, Maurizio (Medicina Historica, 2018)
The following report briefly illustrates the level of development of the treatment of the aortic aneurysm, as it is portrayed in a compendium of general medicine which dates back to the early 20th century.